Pengembangan Clinical Pathway Keperawatan Stroke Berbasis SDKI, SIKI dan SLKI Terhadap Lenght of Stay - Waluyo Waluyo; Yani Indrastuti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Clinical pathway is an integrated service planning concept that summarizes every step given to patients based on medical service standards and evidence-based nursing care with measurable results and within a certain period of time while in hospital. The aim of the research was to develop a clinical pathway for stroke nursing based on SDKI, SIKI and SLKI on length of stay. This study applied a mixed method which consists of two stages. The first stage was to observe 50 nurses in filling out the clinical pathway for stroke nursing in 53 patients for 1 month. Data were analyzed descriptively, then conducted literature studies, conducted FGDs with 20 participants, consulted with 5 experts, compiled a clinical pathway module for stroke nursing based on IDHS, SIKI and SLKI, and compiled SPO clinical pathway for stroke nursing. The second stage was a module trial using a one-group pre-post test design, which involved 51 nurses and 34 stroke patients. Data were analyzed using the Wilcoxon signed rank test. The results of the first phase of the study showed that the implementation of the clinical pathway for stroke nursing before development was included in the good category. The results of the second phase of the study showed that the implementation of the stroke nursing clinical pathway prior to socialization was in the good category, namely 82.99% of nurses obeyed the procedures; while after the socialization it was also included in the good category, namely 90.06% of nurses obeyed carrying out the procedure. The p-value of the Wilcoxon test was 0.000 (there were difference in the application of the stroke nursing clinical pathway between before and after socialization). It was concluded that the clinical pathway resulting from the development had an effect on the length of stay.Keywords: clinical pathway; strokes; nursing; length of stay ABSTRAK Clinical pathway merupakan suatu konsep perencanaan pelayanan terpadu yang merangkum setiap langkah yang diberikan kepada pasien berdasarkan standar pelayanan medis dan asuhan keperawatan yang berbasis bukti dengan hasil yang terukur dan dalam jangka waktu tertentu selama di rumah sakit. Tujuan penelitian adalah  mengembangkan clinical pathway keperawatan stroke berbasis SDKI, SIKI dan SLKI terhadap lenght of stay. Penelitian ini menerapkan mixed method yang terdiri dua tahap. Tahap pertama adalah mengobservasi 50 perawat dalam melaksanakan pengisian clinical pathway keperawatan stroke pada 53 pasien selama 1 bulan. Data dianalisis secara deskriptif, kemudian melakukan studi literatur, melaksanakan FGD dengan 20 partisipan, berkonsultasi dengan 5 pakar, menyusun modul clinical pathway keperawatan stroke berbasis SDKI, SIKI dan SLKI, serta menyusun SPO clinical pathway keperawatan stroke. Tahap kedua adalah uji coba modul menggunakan rancangan one-group pre-post test, yang melibatkan 51 perawat dan 34 pasien stroke. Data dianalisis menggunakan Wilcoxon signed rank test. Hasil penelitian tahap pertama menunjukkan bahwa pelaksanaan clinical pathway keperawatan stroke sebelum pengembangan termasuk dalam kategori baik. Hasil penelitian tahap kedua menunjukkan bahwa pelaksanaan clinical pathway keperawatan stroke sebelum sosialisasi termasuk kategori baik yaitu 82,99% perawat patuh melaksanakan prosedur; sedangkan sesudah sosialisasi juga termasuk kategori baik yaitu 90,06% perawat patuh melaksanakan prosedur. Nilai p dari uji Wilcoxon adalah 0,000 (ada perbedaan penerapan clinical pathway keperawatan stroke antara sebelum dan sesudah sosialisasi). Disimpulkan bahwa clinical pathway hasil pengembangan berpengaruh terhadap lenght of stay.Kata kunci: clinical pathway; stroke; keperawatan; length of stay